The diversity of trophoblast cells and niches of placenta accreta spectrum disorders revealed by single-cell RNA sequencing - Ma, Jingmei; Liu, Yawei; Guo, Zhirong; Sun, Run; Yang, Xinrui; Zheng, Weiran; Ma, Yongdan; Rong, Yin; Wang, Hongmei; Yang, Huixia; Xiao, Zhenyu (Frontiers in Cell and Developmental Biology, 2022)
Placenta accreta spectrum disorders (PAS) are severe pregnancy complications that occur when extravillous trophoblast cells (EVTs) invade beyond the uterine inner myometrium and are characterized by hypervascularity on prenatal ultrasound and catastrophic postpartum hemorrhage. The potential mechanisms remain incompletely understood. With single-cell RNA-sequencing analysis on the representative invasive parts and the normal part obtained from the same PAS placenta, we profiled the pathological landscape of invasive PAS placenta and deciphered an intensified differentiation pathway from progenitor cytotrophoblasts (CTBs) to EVTs via LAMB4+ and KRT6A+ CTBs. In the absence of the decidua, the invasive trophoblasts of various differentiation states interacted with ADIRF+ and DES+ maternal stromal cells. The PAS-associated hypervascularity might be due to the enhanced crosstalk of trophoblasts, stromal cells and vascular endothelial cells. Finally, we presented an immune microenvironmental landscape of invasive PAS. The pathogenesis of PAS could be further explored with current resources for future targeted translational studies.